2004
DOI: 10.1016/j.ejheart.2004.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials update from the Heart Failure Society of America: EMOTE, HERB‐CHF, BEST genetic sub‐study and RHYTHM‐ICD

Abstract: This article summarises key presentations relevant to the pathophysiology, prevention or treatment of heart failure, from the Heart Failure Society of America annual meeting held in Toronto, Canada. Data from the EnoxiMone in intravenous inOTropE-dependent subjects (EMOTE) study suggest that the oral PDE-3 inhibitor enoximone may be effective for weaning severe heart failure patients from intravenous inotropic therapy. Hawthorn Extract Randomised Blinded Trial in CHF (HERB-CHF) failed to show a benefit of hawt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It is reported to have positive inotropic, vasodilator, anti‐ischaemic, anti‐arrhythmic and anti‐oxidant properties. A previous small randomised controlled trial showed no evidence of a beneficial effect of crataegus extract over placebo [13].…”
Section: Survival and Prognosis: Investigation Of Crataegus Extract Wmentioning
confidence: 87%
“…It is reported to have positive inotropic, vasodilator, anti‐ischaemic, anti‐arrhythmic and anti‐oxidant properties. A previous small randomised controlled trial showed no evidence of a beneficial effect of crataegus extract over placebo [13].…”
Section: Survival and Prognosis: Investigation Of Crataegus Extract Wmentioning
confidence: 87%
“…The 30-day time point was selected to allow sufficient time for clinical stabilization and restoration of cardiopulmonary homoeostasis, as reported previously [40]. Similar time points were selected in clinical trials such as EMOTE (EnoxiMone in intravenous inOTropE) investigating the effect of enoximone on the success of weaning chronic inotropic support in patients with advanced heart failure [40]. At 30-days post-therapy, all patients exhibited marked improvement in cardiac function, as evidenced by the improvement from NYHA class IV pre-admission to NYHA class II-III post-treatment and by the 6-min walk test.…”
Section: Discussionmentioning
confidence: 99%
“…The more recent advances in CHF therapy have underlined the importance of the peripheral and autonomic adjustments developed in the syndrome. Intervention that ameliorates only the cardiac function may be harmful if not accompanied by improvements in the compensatory mechanisms, such as neurohormonal activation and ventilatory changes 11 …”
Section: Introductionmentioning
confidence: 99%